Recognition of Customary Law in the Perspective of Legal Politics: A Study of Weak Legal Pluralism in Dayak Society - Mursyida, Aisyah Nurhalisha; Sukti, Surya; Mustar, Mustar (Dinasti Research, 2026)
This study examines the relationship between legal pluralism and legal politics in the recognition of customary law in Indonesia, which remains conditional in practice. The background of this research lies in the diversity of legal systems in Indonesia that creates legal pluralism, while the state continues to exercise control through its legal policies. The novelty of this study is reflected in its critical analysis of the ambiguity of customary law recognition, particularly through the concept of weak legal pluralism as observed in the practices of Dayak indigenous communities in Kalimantan. This research employs a normative legal method using statutory and conceptual approaches. The findings reveal that although Article 18B paragraph (2) of the 1945 Constitution constitutionally recognizes indigenous peoples, such recognition is limited by the conditions “as long as they still exist” and “in accordance with the principles of the Unitary State of the Republic of Indonesia,” which position customary law as subordinate to state law. In practice, customary law continues to function in dispute resolution but requires formal validation from the state. Therefore, a reorientation of legal politics is needed to ensure that the recognition of customary law is not merely formal but also substantive, providing greater autonomy to indigenous communities.